2017
DOI: 10.5694/mja17.00972
|View full text |Cite
|
Sign up to set email alerts
|

Identifying attributes of care that may improve cost‐effectiveness in the youth mental health service system

Abstract: There is at least suggestive cost-effectiveness evidence for a range of attributes of youth mental health care. Further economic research is needed to substantiate most cost-effectiveness findings and to improve targeting of care among young people. Future economic evaluations should examine costs from both societal and health care perspectives and incorporate evidence regarding young people's preferences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 136 publications
(133 reference statements)
0
28
0
Order By: Relevance
“…Progress in economic evidence development in this area remains slow. More evidence is available on psychosis early intervention, which often also covers an adult population and is reviewed later in this paper.…”
Section: Current Economic Evidence and Key Events In Mental Health Carementioning
confidence: 99%
See 2 more Smart Citations
“…Progress in economic evidence development in this area remains slow. More evidence is available on psychosis early intervention, which often also covers an adult population and is reviewed later in this paper.…”
Section: Current Economic Evidence and Key Events In Mental Health Carementioning
confidence: 99%
“…A recent literature review of economic evaluations published between 1997 and 2014 in the UK National Health Service (NHS) Economic Evaluations Database and other sources focused on attributes of care systems (i.e., excluding pharmacological or individual psychological therapies). Forty studies with both costs and outcomes of youth mental health care were identified. These interventions targeted a wide range of mental health problems, including anxiety, depression, eating disorders, psychosis, substance use disorders, unspecified mental health problems, forensic mental health, and suicide and self‐harm.…”
Section: Current Economic Evidence and Key Events In Mental Health Carementioning
confidence: 99%
See 1 more Smart Citation
“…Holistic and timely assessment has been identified as an important and potentially cost‐effective attribute of youth mental health services (Hamilton et al, ). Neurocognitive and symptom assessment specifically, is internationally recognised as important to youth mental health care (Hamilton et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…These att ributes were selected from a longer list identifi ed by a literature review. 18 We based our decisions about which of the att ributes identifi ed in that review to include in the fi nal survey instrument on our subjective judgements regarding where clinician opinion had the most potential to add to existing evidence. For example, acute inpatient care was one of the options identifi ed in the review for implementing crisis support, but we did not explore this in our survey as we felt that health service use data on presentations to acute services would likely provide a bett er guide to the level of need for these services.…”
Section: Methodsmentioning
confidence: 99%